Predictors of depression among caregivers of patients with severe mental illness in Northwest Ethiopia, 2023: an explanatory sequential mixed-method study - Munie, Birhanu Mengist; Birhan, Zelalem; Legas, Getasew; Asnakew, Sintayehu; Belete, Amsalu; Beyene, Getnet Mihretie; Shiferaw, Kirubel; Mulu, Anemut Tilahun; Kassie, Yohannes Tesfahun; Aytenew, Tigabu Munye; Tedla, Assasahegn (Frontiers in Psychiatry, 2024)
Background Severe mental illness results in an enormous social and economic burden on affected individuals, their families, and communities, especially in developing countries, such as Ethiopia. Objective The aim of this study was to assess the level of depression among caregivers of patients with severe mental illness in Debre Tabor Town, Northwest Ethiopia in 2023. Methods This institution-based explanatory mixed study was conducted at Debre Tabor Compressive Specialized Hospitals between September 30 to October 30, 2023. A systematic random sampling technique was used to select 260 study participants, and a public health questionnaire was used to assess depression. Epicollect5 was used to collect data, which were then exported to the SPSS-25 for analysis. Variables with a p-value <0.25 were considered candidates for the multivariate logistic regression analysis. The odds ratios with a 95% confidence interval were used to determine the strength of the association. An in-depth interview was conducted with 11 participants, selected using purposive sampling. Results The prevalence of depression was 31.3% (95% CI = 29.7–38.6). The multivariate analysis showed that being female (AOD = 2.43, CI = 1.42–7.23), divorced/widowed (AOD = 1.8, CI = 1.32–6.34), poor social support (AOD = 2.2, CI = 1.9–5.87), and perceived stigma (AOD = 2.33, CI = 0.24–13.22) were positively associated with depression. The qualitative results suggest that being female, illiterate, severity of the illness, poor social support, and stigma were factors for depression. Conclusions and recommendations The prevalence of depression was high among caregivers of patients with severe mental illness. Female sex, being divorced or widowed, being illiterate, poor social support, and perceived stigma were the contributing factors. This implies that a greater focus on caregivers and the government increases mental health literacy and mental health community services.